Hydro-environmental pollution of Turag river in Bangladesh - Islam, JB; Akter, S; Bhowmick, AC; Uddin, MN; Sarkar, M (Bangladesh Journal of Scientific and Industrial Research, 2018)
The pollution due to minerals and anions in surface water and their settlement tendency on sediment of the Turag river has been studied. Higher concentration of potassium and phosphate ion in surface water and similar deposition on sediment has been recorded. The observed average concentration of Na, K, Cl-, PO4 3- in surface water and in surface sediment was 22.10, 13.20, 108.50, 17.80 mg/L and 1359.07, 2526.10, 37.50, 31.76 mg/kg, respectively. This high concentration of minerals and anions in surface water and sediments indicates that hidro-environment of the Turag river is badly affected.The minerals and ions are strongly correlated (r = 0.99) which implies that they come from similar sources and forcefully added to the river in a regular basis. Principal component analysis reveals that only one principal component is covering more than 99 % of cumulative variance. There are very few variations of parameters in the principal component to indicate that all parameters exert similar effect on hydro-environment and are contributing to deteriorate the ecological balance.These are supported by dendrogram analysis. Bangladesh J. Sci. Ind. Res.53(3), 161-168, 2018